Development of Assessment Instruments in Individual Clothing Production Courses - Retnasari, Dian; Budiastuti, Emy (Universitas Negeri Semarang, 2023)
Learning requires an assessment tool as a standard guideline for assessing student performance. This study aims to develop a set of assessments and knowing the eligibility of assessment in the Individual Fashion Production Course. Development models that adopt 4D procedures are: define, design, develop, and disseminate. Data collection techniques with focus group discussions, observations and interviews. The results of the validity of the contents of the instrument items show that 21 items are valid, of which 18 question items (86%) are included in the very valid criteria (high validity) and 3 question items (14%) are of medium validity. The results of the Kappa analysis showed that the reliability coefficient of the instrument was 0.782. The result of the data acquisition is descriptively obtained the value X = 94, it can be categorized as